Initiation and Training of Adolescent Health Cadres of Poskestren in Mantikulore District City of Palu: Inisiasi dan Pelatihan Kader Kesehatan Remaja Poskestren di Kecamatan Mantikulore Kota Palu - Dwi Erma Kusumawati; Ansar Ansar; Adhyanti Adhyanti (Poltekkes Kemenkes Palu, 2021)
Health promotion in adolescents is one of the alternative solutions to improve the health status of the community. Efforts that can be made in Islamic boarding schools are through the revitalization of Poskestren and adolescent health cadres . This activity aims to initiate and train youth health cadres in Islamic boarding schools. The activity was carried out in September 2021 at the Hidayatullah Tondo Islamic Boarding School and the Liwa'ul Haq Islamic Boarding School in Palu City. The method of activity is through surveys, brain storming and discussion, simulations and demonstrations. The results show that pesantren health posts (Poskestren) have been successfully established in 2 activity locations. There is an increase in the knowledge of Poskestren cadres from before being given training compared to after being given training. It is recommended that this activity can be continued and the need for further training activities with other contents such as basic health, environmental health, reproductive health and others.